Market socialism and economic calculation - Machaj, Mateusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The purpose of this paper is to examine unappreciated criticism of the market socialism model that was developed in the 1930s during the Socialist Calculation Debate. Our aim is to present two related theses: (1) market socialism is not different from the “standard” version of socialism, and as a consequence of that (2) no type of socialism can mimic capitalist market process. The first section briefly summarizes the importance and misunderstandings of the market socialism model. The second section discusses its omitted criticism. The third section contrasts calculation under market socialism with calculations under a capitalist regime. The last section presents concluding comments
Argumenta Oeconomica, 2014, Nr 1 (32), s. 177-196
Keywords: socialist calculation debate; markets; economic systems